النظام اللغوي و ومقتضى الحال و أثرهما في نجاح العملية الاتصالية التواصلية عند الجاحظ من خلا كتابه البيان والتبيين (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The reseach concerning the Arab heritage is an important issue, especially if it is related to a distinguished and a prominent scholar such as Al-Jhaiz, whose works and writings are characterized by excellence, skill, mastery and sophisticated intelligence. He is considered to be a man of knowledge and science, specifically when it comes to rhetorics. As he has a crucial role in giving it interest and granting it a distinguished place.What we aim at in this study is to search a case that we found features related to Al-Jahiz, it is the linguistic system and the appropriatenessof the  case and their impact on the success of the communicative process at Al-Jahiz through his book Al-Bayan and Al-Tabin. key words  -  Appropriateness of the  case -linguistic system – Communication- Connection- concerning -Al-Jahiz